Extratropical Cyclone Precipitation Life Cycles: A Satellite‐Based Analysis. Issue 16 (27th August 2018) - Booth, James F.; Naud, Catherine M.; Jeyaratnam, Jeyavinoth
Abstract: Although extratropical cyclones are the most common midlatitude storms, the relationship between their precipitation life cycle and dynamical strength life cycle has not been thoroughly analyzed. Given that thermodynamic heat exchanges associated with precipitation impact cyclone circulation, there is a need to understand the precipitation/dynamics relationship. Based on Integrated Multi‐satellitE Retrievals for Global Precipitation MeasurementGPM precipitation and Lagrangian cyclone tracks, the precipitation maximum occurs prior to the dynamical strength maximum 70% of the time. The lag in timing is consistent with the difference in cyclone precipitable water vapor at the two peaks. Conditional subsetting of the cyclone composites shows that if the precipitable water vapor distribution is constrained to be equal throughout the composite life cycle, the precipitation peak occurs very near the time of the peak in cyclone dynamical strength. Thus, the boost in dynamical strength caused by latent heat associated with precipitation manifest itself with little to no time lag. Plain Language Summary: Extratropical cyclones are the most common storms in the midlatitudes. These storms generate strong precipitation and winds. The heating within the troposphere that occurs during the formation of the cyclone''s precipitation can increase the cyclone''s circulation strength, which relates closely to the winds. This study analyzes the timing of the evolution of precipitation and cyclone strength using satellite observations of precipitation. The results show that the peak in precipitation usually occurs prior to the peak in circulation, and the cause is related to moisture availability. A separate analysis in which cyclones are selected in a manner that fixes the moisture availability at each time step throughout the life cycle indicates no lag between precipitation and circulation peaks. Thus, it seems likely that any boost in dynamical strength that is caused by the precipitation occurs with little to no lag in time. Key Points: The lag in timing of extratropical cyclone dynamical strength compared to precipitation is explained by changes in environmental moisture The life cycle of precipitation is governed by both cyclone dynamical age and cyclone latitude